Let's boogie [compact disc] (Rainbow Songs Inc., 2015)
Rock 'n' Rainbow supply plenty of catchy hooks and funk-rock rhythms in a family friendly dance party that is full of high energy tunes including The Freeze; I Like to Ride My Bike; and more.